Web Browsers Security Web-Lab - Serrhini, Mohammed (International Journal of Online and Biomedical Engineering (iJOE), 2013)
One of the biggest created software is Web browser, today’s almost is unique software used to access online for lot off electronic transactions services such as e-mail, e-banking, e-commerce, and e-learning etc... Hackers know that browsers are installed into all computers, smart phones, tablets , soon other devices such TV, Cars and others, they can be used to compromise all this devices, all browsers have enabled or disabled features that define theirs behaviors for executing good material and stopping malicious ones, unfortunately most of users are unwilling to setup this features correctly to enhance theirs safety, because many of them still do not understand even basic security concepts. This paper presents Web Browsers Security Web-Lab where student can practice and test online the real security threat that he was or could be exposed with his browser, we describe a two part for achieving this work, first an application launched at student side that will automatically detect all installed browsers and theirs features setting in his computer and based on the finding prepare to him an online tailored security awareness practicing work program and second Web-Lab platform where he can practice and test all security hole and risk if he browse the web with such enabled or disabled feature in his browser.